When There Is No More Music...or...Dumagat Internal Refugees in The Philippines and The Issues of "Cultural Objecthood" - Jonas Baes, (Wacana Seni Journal of Arts Discourse, 2012)
In 2002, groups of disparate "indigenous" peoples from the Southern Tagalog region of the Philippines sought refuge somewhere in the Cavite province to escape escalating armed conflict in their localities. Among these groups of people were the Dumagat from the Rizal Province. Long absorbed into the national body politic that has resulted to the loss of an indigenous way of life, this particular Dumagat group disappears from the eyes of the culture brokers as a "cultural object." The purpose of this article is twofold. On the one hand, it aims to interrogate the praxis of ethnomusicology set amidst the backdrop of a culture industry emanating mainly, if not entirely, from the state and its apparatuses. On the other hand, it explores the avenues by which ethnomusicology might be able to refunction, in realising the social realities faced by some of its chosen subjects.